Simvastatin therapy in climacteric women with atherogenic dyslipoproteinemias - N. V. Izmozherova; A. A. Popov (Российский кардиологический журнал)
The study aimed to assess real-world clinical practice effectiveness and safety of simvastatin therapy in climacteric women. A prospective cohort study included 82post-menopausal women with lipid-lowering therapy indications; median age 56,5 (52,0-60,0) years. Simvastatin therapy lasted for one year. After three months of the treatment, total cholesterol (TCH) level significantly reduced, due to decreased low-density lipoprotein (LDL) CH, athemgenicity index decreased, and high to low-density lipoprotein CH ratio increased. Levels of triglycerides and high-density lipoprotein CH remained the same, as well as liver enzyme activity. Neuro-vegetative symptoms of climacteric syndrome become less manifested. Ln climacteric women, long-term simvastatin therapy controlled lipid metabolism effectively and safely.